Simple and ecofriendly synthesis of dihydropyrimidinones (thiones), dihydropyridines, and pyridines using 3-formylchromones as substrates assisted by a recyclable Preyssler heteropolyacid - Sanchez, Laura Mabel (2016)
Several dihydropyrimidinones/thiones, 1,4-dihydropyridines, and pyridine derivatives were prepared in very good yields and purity values. The corresponding reactions were carried out by employing a bulk Preyssler heteropolyacid H14[NaP5W29MoO110] as an efficient and recyclable catalyst. The preparation of pyridine derivatives was carried out not through a usual procedure, i.e., the opening of the γ-pyrone ring of 3-formylchromone. In general, reactions took place in solvent-free conditions at 80°C during short reaction times.